Madras Metropolitan Area Travel Corridors - 1991 Report - Planning Commission (Planning Commission Government of India, 1971)
The Madras Metropolitan Area Travel Corridors – 1991 Report examines the growing transportation challenges arising from rapid population growth and increasing commuter demand in the Madras Metropolitan Area. With the population projected to reach 5.3 million by 1991, the report highlights severe pressure on existing mass transport systems, particularly state-run bus services and suburban railways, which are already operating beyond their designed capacities. Based on an analysis of daily travel patterns and projected passenger volumes, the study identifies eight major travel corridors, with the North–South–Eastern Corridor emerging as the most critical due to its exceptionally high commuter load. The report recommends the development of a high-capacity rapid transit system for priority corridors, supported by techno-economic feasibility studies, while optimizing existing bus and rail services in other areas. Overall, the report emphasizes the urgency of comprehensive, long-term transportation planning to ensure efficient, sustainable, and cost-effective urban mobility in Madras.
Government of India Metropolitan Transport Team Planning Commission November, 1971
Government of India Metropolitan Transport Team Planning Commission November, 1971
Keywords: Madras Metropolitan Area; Urban Transport Planning; Travel Corridors; Population Growth; Commuter Demand; Mass Transportation; Bus and Suburban Rail; Rapid Transit System; Transport Infrastructure; Traffic Congestion; Corridor Analysis; Sustainable Urban Mobility